A study of weathered coal spectroscopic properties. (September 2017) - Krumins, Janis; Yang, Zhiping; Zhang, Qiang; Yan, Min; Klavins, Maris
Abstract: Current coal industry causes significant environmental pollution and the most air pollution deaths in the world, making the development of new eco-friendly applications one of the top priorities. Coal contains up to 50 % humic substances (HS), the majority of which is humic acid (HA). HA is well known for its beneficial properties and thus compounds extracted from coal can be used to develop new applications. To address this issue, we assessed structural composition of coal HS by measuring their spectroscopic properties. As the result, obtained spectra can be used to identify information about the molecules and thus allowing describing the composition of HS. The purpose of this study was to identify HS properties of weathered coal in regards to finding new uses for this otherwise neglected natural resource. The results show that weathered coal contains relatively high oxygen content and indicate transformations of O-containing functional groups. Weathered coal has high amount of bioactive molecules as well as condensed aromatics. The major coal forming compounds are acridine, anthracene, perylene, tetracene and naphthalene and it does not depend upon where the study site is located.